Artificial Pancreas Systems for People With Type 2 Diabetes: Conception and Design of the European CLOSE Project. (March 2019) - Schliess, Freimut; Heise, Tim; Benesch, Carsten; Mianowska, Beata; Stegbauer, Constance; Broge, Björn; Gillard, Pieter; Binkley, George; Crône, Véronique; Carlier, Sébastien; Delval, Cécile; Petkov, Anton; et al.
In the last 10 years tremendous progress has been made in the development of artificial pancreas (AP) systems for people with type 1 diabetes (T1D). The pan-European consortium CLOSE (Automated Glu c ose Contro l at H o me for People with Chronic Disea se ) is aiming to develop integrated AP solutions (APplus) tailored to the needs of people with type 2 diabetes (T2D). APplus comprises a product and service package complementing the AP system by obligatory training as well as home visits and telemedical consultations on demand. Outcome predictors and performance indicators shall help to identify people who could benefit most from AP usage and facilitate the measurement of AP impact in diabetes care. In a first step CLOSE will establish a scalable APplus model case working at the interface between patients, homecare service providers, and payers in France. CLOSE will then scale up APplus by pursuing geographic distribution, targeting additional audiences, and enhancing AP functionalities and interconnectedness. By being part of the European Institute of Innovation and Technology (EIT) Health public-private partnership, CLOSE is committed to the EIT "knowledge triangle" pursuing the integrated advancement of technology, education, and business creation. Putting stakeholders, education, and impact into the center of APplus advancement is considered key for achieving wide AP use in T2D care.